2017
DOI: 10.3982/ecta14330
|View full text |Cite
|
Sign up to set email alerts
|

Value of Persistent Information

Abstract: We develop a theory of how the value of an agent's information advantage depends on the persistence of information. We focus on strategic situations with strict conflict of interest, formalized as stochastic zero‐sum games where only one of the players observes the state that evolves according to a Markov operator. Operator Q is said to be better for the informed player than operator P if the value of the game under Q is higher than under P regardless of the stage game. We show that this defines a convex parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…However, since the principal can commit ex ante, he can choose an ex-ante optimal mechanism and commit to ignore his private information. More information can hurt if the designer cannot commit not to use the additional piece of information, which is related to the ratchet effect in general and more recently Peski-Toikka (2017). And even if the offered mechanism reveals his private information, the mechanism designer can still commit in the beginning of the first period.…”
Section: Resultsmentioning
confidence: 99%
“…However, since the principal can commit ex ante, he can choose an ex-ante optimal mechanism and commit to ignore his private information. More information can hurt if the designer cannot commit not to use the additional piece of information, which is related to the ratchet effect in general and more recently Peski-Toikka (2017). And even if the offered mechanism reveals his private information, the mechanism designer can still commit in the beginning of the first period.…”
Section: Resultsmentioning
confidence: 99%
“…It is known for p ∈ [1/2, 2/3] and some specific values Pęski and Toikka (2014). have recently shown that this value is non-increasing in p, andBressaud and Quas (2014) have determined the optimal strategies for values of p up to ∼ .7323.…”
mentioning
confidence: 99%
“…It is known for p ∈ [1/2 2/3] and some specific values Pęski and Toikka (2014). have recently shown that this value is nonincreasing in p, andBressaud and Quas (2014) have determined the optimal strategies for values of p up to ∼ 0 7323.…”
mentioning
confidence: 99%